"But you don't look sick:" Memorable messages of emerging adulthood autoimmune disease. (June 2023) - Gunning, Jacqueline N.
Background: Experiencing the onset of autoimmune disease in emerging adulthood is disruptive and difficult to make sense of because youth and illness are not expected to co-exist. As a result, emerging adults with autoimmune disease are susceptible to messages that discredit and deny their health experiences. Though communication research has explored dismissive and disenfranchising communication in the face of chronic illness, a need for how to disrupt and replace this harmful or inadequate messaging remains.Purpose: Building upon prior memorable messages research that centers the call "I wish, " asking individuals not only about messages received but messages desired, the present study identifies harmful and helpful memorable messages in the face of autoimmune disease onset and diagnosis.Research Design: Guided by Cooke-Jackson & Rubinsky's (2021) theory of memorable messages and call for research on message disruption, the present study explores the messages 25 assigned female at birth (AFAB) individuals with autoimmune disease received during their illness journeys using individual, semi-structured interviews.Results: Findings reveal messages of dismissal, blame, and presumed psychosis (e.g., "it's all in your head, " "but you look healthy") as characterizing the diagnostic journey. Participants identify messages of belief, support, and interest (e.g., "I believe you, " "you are not alone, " "help me understand") as being helpful while navigating their disease.Conclusion: Findings illuminate how family members, friends, health care providers, intimate partners, and relational others can effectively support emerging adults navigating a difficult and disruptive health experience. Limitations and future directions are discussed.